Try substituting those values, and you will see they do not fit either equation.
looking at the 2nd equation, y = x+2, so
x+2 = x^2+5x-3
x^2 + 4x - 5 = 0
(x+5)(x-1) = 0
x = -5 or 1
so, y = -3 or 3
the solutions are thus (-5,-3)(1,3)
Hope this helps
Please give me Brainliest
formula for volume of a sphere is V=4/3 x pi x R63
if diameter = 16 than radius = 16/2 = 8
so the equation would be 4/3 x pi x 8^3
The question is an illustration of sample and population, and the estimate of the population of squirrel in the park is 55
<h3>How to determine the population of squirrel?</h3>
The given parameters are:
Marked squirrels = 43
Captured squirrels = 50
Of the 50 captured squirrels, 38 are from the marked squirrels.
This means that the number of unmarked squirrels is:
Unmarked = 50 - 38
Evaluate
Unmarked = 12
The population of the squirrel is then calculated using:
Population = Marked + Unmarked
So, we have:
Population = 43 + 12
Evaluate the sum
Population = 55
Hence, the estimate of the population of squirrel in the park is 55
Read more about population at:
brainly.com/question/7301139
#SPJ1
Answer:
The work is in the explanation.
Step-by-step explanation:
The sine addition identity is:
.
The sine difference identity is:
.
The cosine addition identity is:
.
The cosine difference identity is:
.
We need to find a way to put some or all of these together to get:
.
So I do notice on the right hand side the
and the
.
Let's start there then.
There is a plus sign in between them so let's add those together:
![\sin(a+b)+\sin(a-b)](https://tex.z-dn.net/?f=%5Csin%28a%2Bb%29%2B%5Csin%28a-b%29)
![=[\sin(a+b)]+[\sin(a-b)]](https://tex.z-dn.net/?f=%3D%5B%5Csin%28a%2Bb%29%5D%2B%5B%5Csin%28a-b%29%5D)
![=[\sin(a)\cos(b)+\cos(a)\sin(b)]+[\sin(a)\cos(b)-\cos(a)\sin(b)]](https://tex.z-dn.net/?f=%3D%5B%5Csin%28a%29%5Ccos%28b%29%2B%5Ccos%28a%29%5Csin%28b%29%5D%2B%5B%5Csin%28a%29%5Ccos%28b%29-%5Ccos%28a%29%5Csin%28b%29%5D)
There are two pairs of like terms. I will gather them together so you can see it more clearly:
![=[\sin(a)\cos(b)+\sin(a)\cos(b)]+[\cos(a)\sin(b)-\cos(a)\sin(b)]](https://tex.z-dn.net/?f=%3D%5B%5Csin%28a%29%5Ccos%28b%29%2B%5Csin%28a%29%5Ccos%28b%29%5D%2B%5B%5Ccos%28a%29%5Csin%28b%29-%5Ccos%28a%29%5Csin%28b%29%5D)
![=2\sin(a)\cos(b)+0](https://tex.z-dn.net/?f=%3D2%5Csin%28a%29%5Ccos%28b%29%2B0)
![=2\sin(a)\cos(b)](https://tex.z-dn.net/?f=%3D2%5Csin%28a%29%5Ccos%28b%29)
So this implies:
![\sin(a+b)+\sin(a-b)=2\sin(a)\cos(b)](https://tex.z-dn.net/?f=%5Csin%28a%2Bb%29%2B%5Csin%28a-b%29%3D2%5Csin%28a%29%5Ccos%28b%29)
Divide both sides by 2:
![\frac{\sin(a+b)+\sin(a-b)}{2}=\sin(a)\cos(b)](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csin%28a%2Bb%29%2B%5Csin%28a-b%29%7D%7B2%7D%3D%5Csin%28a%29%5Ccos%28b%29)
By the symmetric property we can write:
![\sin(a)\cos(b)=\frac{\sin(a+b)+\sin(a-b)}{2}](https://tex.z-dn.net/?f=%5Csin%28a%29%5Ccos%28b%29%3D%5Cfrac%7B%5Csin%28a%2Bb%29%2B%5Csin%28a-b%29%7D%7B2%7D)